Discoveries in the Arctic Sea 1913-1914 and 1917-1918 / positions deduced and mapped by the Geodetic Survey of Canada - Geodetic Survey of Canada (Geodetic Survey of Canada, 1921)
Shows routes of Leffingwell-Mikkelsen, R.A. Bartlett, S.T. Storkerson. Copy 1: Annotated in ink by Stefansson to show the varying locations of "Keenan Land" as depicted on different charts, and the location of "Takpuk Island." Cope 2: Annotated in pencil and ink. Relief shown by hachures and spot heights. Deptsh shown by soundings. Base map: "Arctic Coast of Alaska C & GS 9400" from the US Coast and Geodetic Survey. Fold out map removed from: "The Friendly Arctic : the story of five years in polar regions" by Vilhjalmur Stefansson, 1921. Indexed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography. Color